KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN DENGAN KEPUASAN PASIEN SEBAGAI MEDIASI PASIEN RAWAT INAP DI RSU DEWI SARTIKA KENDARI - Isfan, Randa Wula; Fauziah, Yulianti (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Hospital is one of the healthcare facilities, in the rapid technological development and increasingly fierce competition Hospital is required to continue to improve the quality of services that meet the needs of patients. This study aims to determine the effect of service quality on patient loyalty with patient satisfaction as mediation of hospitalized patients at Dewi Sartika Kendari General Hospital.The research method used was associative, with a cross-sectional design. Sampling technique used purposive sampling. Samples used were 83 respondents inpatients at Dewi Sartika Kendari General Hospital with data analysis using SPSS with path analysis method.The results showed that: a) Service quality had a positive and significant effect on patient satisfaction, the value of the effect was 0.583 and a significance of 0.000 <0.05. b) Quality of service does not have a positive and significant effect on patient loyalty, the value of the influence is 0.164 and the significance is 0.106> 0.05. c) Patient satisfaction has a positive and significant effect on patient loyalty, the value of the influence is 0.575 and a significance of 0.000 <0.05. d) Service quality has a positive and significant effect on patient loyalty with patient satisfaction as a mediating variable with a direct influence value of 0.164 <from the indirect effect value of 0.335